1980
DOI: 10.1111/j.1467-1770.1980.tb00323.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF BENZODIAZEPINE (VALIUM) ON PERMEABILITY OF LANGUAGE EGO BOUNDARIES 1

Abstract: This study was designed as an extension of previous research in which pronunciation of a foreign language was experimentally manipulated using alcohol or hypnosis, t o confirm a relationship between permeability of language ego boundaries and pronunciation. The present study used Benzodiazepine (Valium) to manipulate pronunciation in Thai. Seventy-five subjects were assigned to one of four treatment conditions: Placebo, 2 mg., 5 mg., or 10 mg., and subsequently tested on the Standard Thai Procedure (STP) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In the experiments using alcohol , they found clear evidence that moderate amounts of alcohol insigni®cantly lowered mental reasoning while signi®cantly improving oral production skills. Studies with Valium (Guiora et al, 1980) and hypnosis (Schumann et al, 1978) found similar, though not as strong, results. While this is interesting evidence, it suffers from two weaknesses.…”
Section: Inhibition and Language Learningsupporting
confidence: 63%
“…In the experiments using alcohol , they found clear evidence that moderate amounts of alcohol insigni®cantly lowered mental reasoning while signi®cantly improving oral production skills. Studies with Valium (Guiora et al, 1980) and hypnosis (Schumann et al, 1978) found similar, though not as strong, results. While this is interesting evidence, it suffers from two weaknesses.…”
Section: Inhibition and Language Learningsupporting
confidence: 63%
“…In experimental studies of this hypothesis, Guiora and his colleagues demonstrated that reduced inhibition led to increased oral proficiency in a foreign language. When students were given moderate amounts of alcohol (Guiora, Beit-Hallahmi, Brannon, Dull, & Scovel, 1972), valium (Guiora, Acton, Erard, & Strickland, 1980), or placed under hypnosis (Schumann, Holroyd, Campbell, & Ward, 1978), they performed better at pronouncing a foreign language while exhibiting insignificant decreases in mental reasoning capabilities. Not surprisingly, however, these techniques have not found their way into the average classroom!…”
Section: Participation In Language Learning Environmentsmentioning
confidence: 99%
“…In contrast to alcohol, the sedative drug valium did not affect performance on a pronunciation test or lower inhibition [19]. Subjects under deep hypnosis perform better on learning tasks than those under lesser types of hypnosis [20].…”
Section: Lowered Inhibitionmentioning
confidence: 92%
“…It is thought that these deficits occur due to increased grammatical and pronunciation errors. However, some anxiety also promotes language acquisition [19]. Thus, we can conclude that alcohol should be consumed in small amounts.…”
Section: Lowered Inhibitionmentioning
confidence: 99%